Inoculação e doses de fósforo em feijão caupi no sul do Estado do Tocantins - Rocha, Weslany Silva (Universidade Federal do Tocantins, 2017)
The cowpea through symbiosis with the bacteria of the genus Bradyrhizobium can obtain N through the process of biological nitrogen fixation (BNF) that is one way to increase legumes productivity avoiding costs with soluble nitrogen fertilizers. Nutritional deficiencies can interfere on the BNF, because most of the tropical soils are deficient in phosphorus and phosphorus has effect on nitrogenase activity. This study aimed to evaluate phosphorus doses in cowpea under greenhouse and field conditions, with and without inoculants. The experiments were conducted during 2014/15 crop year at Federal University of Tocantins with the variety of cowpea BRS Nova Era. The inoculation with a standard strain already recommended for cowpea was done for posterior evaluation. An experimental design of randomized blocks in a 2 x 6 factorial arrangement was used, being the first factor (with and without inoculant) and the second factor six doses of phosphorus (0, 30, 60, 90, 120 e 150 kg ha-1 de P2O5), totalizing 12 treatments with three repetitions in greenhouse and a randomized blocks with four repetitions in the field, crop 2014/15. The characteristics evaluated in greenhouse conditions were: shoot dry mass, root dry mass, nodule number and dry mass and phosphorus accumulation in the shoot. The characteristics evaluated in field conditions were: flowering, total chlorophyll, root dry mass, nodule number, nodule dry mass, shoot dry mass, one hundred seeds weigh, productivity and phosphorus accumulation in the shoot. Inoculation and phosphorus application together increased root dry mass in the cowpea cultivar Nova Era. The dose of phosphorus with inoculant that reached the maximum production of shoot dry mass, root dry mass and phosphorus accumulation in the shoot was 150 kg ha-1 of P2O5, in the greenhouse. Phosphorus fertilization had a positive influence on the variables: nodule number and productivity of cowpea grains for the region of Gurupi-TO; for the variables of nodule number and productivity of cowpea, cv BRS Nova Era, was observed a better adjustment of linear equation that shows potential response of the culture to phosphorus fertilization.